Development of Rice Marketing Channels for Large-Scale Farmers to Promote Grassroot Economy: A Case Study of Chang Thong Sub-District, Nakhon Ratchasima Province - Maneenate, Supawadee; Songsiengchai, Patchaya; Loetyingyot, Siriporn; Wichian , Aayarat (Siam University Journal of Business Administration, 2025)
This research aimed to 1) investigate marketing strategies, identify challenges, and explore management approaches for local rice marketing, and 2) develop marketing channels for local rice. Employing a qualitative, participatory action research methodology, this study gathered data from key informants, including members of a large-scale rice farming community enterprise, local rice buyers, and network partners. Data collection methods encompassed field surveys, document analysis, interviews, focus group discussions, problem and potential analysis workshops, and marketing support activities. The findings indicated that 1) rice sales primarily occurred through three marketing channels: the seed rice market, the paddy rice market, and the milled rice market. Key stakeholders in these channels included farmers, local aggregators, rice mills, rice seed centers, and consumers. 2) In terms of developing local rice marketing channels, the farmers prioritized the milled rice channel, as it offered the highest value addition to their rice products and aligned with the group's capabilities and context. The channel development process facilitated collective learning and collaborative problem-solving through integrated actions. This, in turn, led to the creation of tools, mechanisms, and processes that tangibly established a network connecting local rice markets. Consequently, three sales formats and six marketing channels including consignment retail sales, direct retail sales to consumers, and wholesale sales to hotels, These channels enabled the distribution of rice products from farmers to local businesses and consumers, thereby contributing to increased farmer income.